Salesperson Professional Selling and the Effect on Buyer and Salesperson Relationship - Wan Omar, Maznah; Jusoff, Kamaruzaman; Mohd Ali, Mohd Noor (2009)
Regardless of the growing importance and emphasis on relationship marketing, a complete operation of this concept is still unclear. There is a lack of studies that explore the impact of factors such as salesperson professional selling on customer loyalty. This study seeks to verify the relationship between salesperson knowledge and adaptive selling. Computer retail customers with different cultural backgrounds were used as respondents in this study. Respondents were asked to rate their evaluations of customer loyalty towards the salesperson knowledge and adaptive selling skills through a self-administered questionnaires which were written in English language and Bahasa Malaysia. Correlation analyses with Pearson’s r coefficient were performed to identify the degree of one variable’s position that occupies the same relative position on another variable. In addition, preliminary analyses were carried out to ensure no violation of the assumptions for linearity, normality, and homoscedasticity. No violations of the assumptions were found. The results of inter-correlation variables of the study indicate that the salesperson professional selling abilities which comprise of salesperson knowledge and adaptive selling managed to show a strong relationship with customer loyalty.